The Effect of Using Pictures on Students’ Vocabulary Mastery at the Eighth Grade of SMP Negeri 5 Bayan - Agus Yanto; Heri Hidayatullah; I Made Permadi Utama (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Vocabulary mastery plays an important role in supporting students’ English language learning because it influences their ability to understand and communicate effectively. However, many junior high school students still experience difficulties in understanding, remembering, and using English vocabulary appropriately. Therefore, appropriate instructional media are needed to facilitate vocabulary learning and increase students’ engagement. This study aimed to investigate the effect of using pictures on students’ vocabulary mastery at the eighth grade of SMP Negeri 5 Bayan in the 2025/2026 academic year. This study employed a pre-experimental research design using a one-group pre-test and post-test design. The participants consisted of 19 eighth-grade students selected as the research sample. Data were collected through vocabulary tests administered before and after the implementation of picture media. The collected data were analyzed using descriptive statistics and paired sample t-test with the assistance of SPSS 15.0. The findings revealed that students’ vocabulary achievement improved after the implementation of picture media. The mean score increased from 32.21 in the pre-test to 50.32 in the post-test. The paired sample t-test showed a statistically significant difference between pre-test and post-test scores (t = -5.204, p < .001), indicating that picture media had a significant positive effect on students’ vocabulary mastery. In conclusion, the use of pictures can be considered an effective instructional medium to improve students’ vocabulary learning outcomes. The findings contribute to the growing evidence regarding visual-based vocabulary instruction and provide practical implications for English teachers in implementing accessible and engaging strategies for vocabulary learning.